A bibliometric approach to digital innovation in Islamic philanthropy, 2014–2024 - Ferdiansyah, Nizar; Faisal, Yudi Ahmad; Cupian, Cupian; Apriliadi, Ardi (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2025)
This study aims to analyze research trends related to digital innovation in Islamic philanthropy using a bibliometric approach. By utilizing data from Scopus, the study identifies trends in publications and contributions from researchers, institutions, countries, and key journals within this topic. The analysis used the Biblioshiny application from the Bibliometrix R package, facilitating effective data visualization. The findings indicate that adopting digital technologies, such as blockchain, crowdfunding, and fintech, has significantly expanded the scope of Islamic philanthropy. Indonesia and Malaysia dominate research in this field, with notable contributions from institutions and authors. Keywords such as zakat, waqf, and trust have emerged as central themes. The study identifies thematic clusters, including foundational themes like waqf and zakat, and emerging themes like shariah compliance, to provide a comprehensive understanding of the field. Public interest statements This study highlights how countries like Indonesia and Malaysia have emerged as leaders in researching and implementing digital innovations in Islamic philanthropy, focusing on key themes such as trust, zakat, and waqf. Furthermore, the study identifies significant trends and emerging areas, such as Sharia compliance, providing strategic insights into the potential development of digital aspects in Islamic philanthropy studies.